Analisis Industri Otomotif di Provinsi DKI Jakarta, Jawa Barat, Jawa Tengah dan Jawa Timur - Rizky Akbar P; Nurul Istifadah (MediaTrend, 2020)
The automotive industry is one of the most important driving forces of economic growth. The development of the automotive industry in the provinces of DKI Jakarta, West Java, Central Java and East Java is very strategic, so the purpose of this study is to test and analyze the inputs that have a significant effect on the output of the automotive industry in the area. The method used is panel data regression for the period 2010-2014 because it follows the 2009 KBLI. The automotive industry ISIC code is 29100-29300 and 30911-30912. Estimation results show that capital, labor, raw material and energy inputs have a significant positive effect on the output of the automotive industry. This means that Cobb Douglas's theory can be used to explain automotive production in the area.